The 1st JOOUST International Scientific Conference - Jaramogi Oginga Odinga University of Science and Technology (Jaramogi Oginga Odinga University of Science and Technology, 2015)
I take this opportunity to welcome you all to the 1st JOOUST International Scientific Conference starting from 24th to 26thJune, 2015 at Jaramogi Oginga Odinga University of Science & Technology (JOOUST), Bondo Main Campus. JOOUST as one of the nationally designated Science and Technology institution recognizes its important role in the enhancement of science and technology to complement the national efforts of spurring economic growth. The conference theme “Harnessing science, technology and innovation for sustainable development and good governance” provides a forum for a crosssectionalmultidisciplinary discourse among scientists thereby advancing progress in areas that have potential to advance livelihoods,both locally and internationally. The conference brings together research peers from local and international institutions to discuss, share and disseminate research outputs and innovations under five sub-themes namely: 1. Renewable Energy, Environment and Climate Change 2. Governance, Culture and Indigenous Knowledge 3. Agriculture, Food Security and Biodiversity 4. Education & Entrepreneurship 5. Emerging Issues in Health Sciences and Impact Pathways for Science Research This forum is expected to create a platform for the University and like-minded institutions and their researchers to disseminate their ongoing findings and contributions for the advancement of society. Additionally, the conference will create a forum for constantly improving the University’s approach to development-oriented scientific research. It is my hope the deliberations of this conference will provoke policy makers to appreciate the need for substantial and long-term investments in scientific research, innovation and industrialization. I therefore encourage you to be proactive in the conference deliberations and make your earnest contributions for the success of this very important event in the JOOUST calendar. You are also invited to enjoy the serene environment and hospitality of thisUniversity community and its environs. Once again, I warmly welcome you all to this inaugural JOOUST Scientific conference and look forwardto interactive and enjoyable sessions. Prof. Stephen G. Agong’,Ph.D, FAAS Vice Chancellor Jaramogi Oginga Odinga University of Science & Technology (JOOUST)
Harnessing science , technology and innovation for sustainable development and good governance
Programme and abstracts
Keywords: 1st JOOUST International Scientific conference